IMPLEMENTASI METODE QIRO’ATI DALAM PEMBELAJARAN MEMBACA AL-QUR’AN DI TPQ AN-NUR SUMBERTAMAN KOTA PROBOLINGGO - Faridatul Mahwiyah; Benny Prasetiya (LPPM STAI Muhammadiyah Probolinggo, 2023)
The purpose of this study is to analyze and describe more about the process of applying the Qiro'ati method in reading the Koran at TPQ An-Nur Sumber Taman Kota Probolinggo. This research was conducted at TPQ An-Nur Sumber Taman with the research subjects being ustadz/ustadzah TPQ An-Nur Sumber Taman Kota Probolinggo, as well as the impressions of the santri guardians. The techniques used in data collection are: observation, interviews and documentation. This interactive analysis is a data collection technique that is used with various steps such as data reduction, data presentation, and also drawing conclusions. The results of this study are in the form of information regarding the Qiro'ati method and it is applied at TPQ An-Nur Sumber Taman. As for the results obtained, namely, the Qiro'ati method has implemented a system and also a reading technique directly without having to spell it out first, namely smoothly, precisely, quickly, correctly and tartil in accordance with the knowledge of recitation, the learning and teaching models that exist in the method Qiro'ati uses visual aids for classical teaching which contain material in Qiro'ati's volume book.Keywords: Implementation, Qiroati Method, Read Al-Qur'an